Patriarki dalam Perspektif Pesantren Studi Kasus di Pondok Pesantren Bustanul Ulum Mlokorejo - Sinta Bella; Nasihatul Mahmudah; Faiz Azizi; Eli Rahmawati (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Pesantren as a traditional Islamic educational institution has a social and cultural structure that is still thick with patriarchal values. Gender relations in them are often shaped by religious understanding that places men as the main authority. This study aims, first, to describe patriarchy in the perspective of pesantren. Second, to analyze and describe patriarchy in pesantren perspective in PP. Bustanul Ulum Mlokorejo. This research uses a qualitative approach with a case study method. The data collection techniques used were observation, documentation, and interviews. The results showed that first, patriarchy in the pesantren perspective is a relationship of male domination over women in socio-religious activities in the pesantren environment. Second, patriarchy in the pesantren perspective is not adopted in PP. Bustanul Ulum Mlokorejo. The implications of this finding indicate the need for dissemination related to relations that are starting to be equal, based on willingness, and mutual cooperation in the pesantren environment. Pesantren is no longer a religious educational institution that is the basis of patriarchal relations.